Advancing and Inspiring Health Economics: A Special Issue in Honor of Tor Iversen - ELINE AAS; Geir Godager; Terje P. Hagen; Unto Häkkinen; Martin Karlsson; Sverre Kittelsen; Henning Øien; Kim Rose Olsen (University of Oslo, 2023)
Professor Tor Iversen is a distinguished and highly respected health economist who has made significant contributions to the field of health economics. With this special issue, we celebrate his work.